Cartoon Puppet Video Media in Supporting Online Learning in Group B2 - Nabila Sindy Pratiwi; I Made Tegeh; Nice Maylani Asril (Journal of Education Technology, 2025)
The listening ability of kindergarten students is still relatively low, which is caused by the lack of media that is able to stimulate students' listening skills, coupled with the challenges of online learning. This research aims to develop cartoon video media as a means of online learning to improve the listening ability of B2 group students. This type of research is development research (R&D) using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The research subjects consisted of two media experts, two material experts, two practitioners (teachers), and 12 students of the B2 group. Data was collected using questionnaires, then analyzed quantitatively and qualitatively. The results of the study showed that the learning videos developed were declared valid with very good qualifications, with a validation score from media experts of 92.7%, material experts of 90.5%, practitioners (teachers) of 90.2%, and student responses of 78.1%. Based on these results, it can be concluded that the cartoon video media developed has a high level of validity and is suitable to be used to support online learning in improving the listening ability of B2 group students. The implication of this study on learning is that cartoon puppet video media can be an innovative alternative in online learning at the kindergarten level. Teachers can more easily build children's attention and interest in listening activities, so that the learning process becomes more effective and fun.